Ways forward for aquatic conservation: Applications of environmental psychology to support management objectives. (15th January 2016) - Walker-Springett, Kate; Jefferson, Rebecca; Böck, Kerstin; Breckwoldt, Annette; Comby, Emeline; Cottet, Marylise; Hübner, Gundula; Le Lay, Yves-François; Shaw, Sylvie; Wyles, Kayleigh
Abstract: The success or failure of environmental management goals can be partially attributed to the support for such goals from the public. Despite this, environmental management is still dominated by a natural science approach with little input from disciplines that are concerned with the relationship between humans and the natural environment such as environmental psychology. Within the marine and freshwater environments, this is particularly concerning given the cultural and aesthetic significance of these environments to the public, coupled with the services delivered by freshwater and marine ecosystems, and the vulnerability of aquatic ecosystems to human-driven environmental perturbations. This paper documents nine case studies which use environmental psychology methods to support a range of aquatic management goals. Examples include understanding the drivers of public attitudes towards ecologically important but uncharismatic river species, impacts of marine litter on human well-being, efficacy of small-scale governance of tropical marine fisheries and the role of media in shaping attitudes towards. These case studies illustrate how environmental psychology and natural sciences can be used together to apply an interdisciplinary approach to the management of aquatic environments. Such an approach that actively takes into account the range of issues surrounding aquatic environment management is more likely to result in successful outcomes, from both human and environmental perspectives. Furthermore, the results illustrate that better understanding the societal importance of aquatic ecosystems can reduce conflict between social needs and ecological objectives, and help improve the governance of aquatic ecosystems. Thus, this paper concludes that an effective relationship between academics and practitioners requires fully utilising the skills, knowledge and experience from both sectors. Highlights: Freshwater and marine conservation benefits from contributions from the social sciences. Societal importance of aquatic environments drives integrated approaches to management. We identify how environmental psychology can support management of aquatic environments. Relationships between academics and practitioners can aid knowledge exchange. Overcoming interdisciplinarity issues can maximise sustainable management outcomes.